La interculturalidad como eje transversal en el aprendizaje de la lecto escritura de los niños de educación inicial 2 de la U.E ´´Ing. Hermel Tayupanda’’ de la comunidad San Jacinto de Culluctus, parroquia Sicalpa, cantón Colta, provincia de Chimborazo, año lectivo 2014-2015’’ - Malán Yautibug, Ana Lucía (2016)
In response to the intercultural, multicultural and multilingual character of our country, The purpose of this paper research is to propose the use of methodological strategies for improving the process of multiculturalism, as a central focus in learning reading and writing in Children of Early Education 2 of the Educative Unit "Ing. Hermel Tayupanda" of the Community of San Jacinto de Culluctus Sicalpa parish, Colta county, Chimborazo province; Institution that has not been given the real importance of multiculturalism as a foundation for learning process in literacy. This is due to a lack of teachers with intercultural identity that handle the two linguistic codes, (Kichwa-Ingles), making it difficult to promote talents, skills, abilities and values held by Children Early Education 2 by the limited capacity to communicate orally. In recent years it has aroused great concern about the different factors that influence the formation and development of the habits of reading and poor writing implementation of viable strategies for teaching methodology is noticed, it has stated in Statistical Reference Test Results Assessment System and Accountability, Applied level students in the province by La DIPEIBCH and nationally by the ME, Whose results have been limited, that justifies the research.